Studi Meta Analisis Pengaruh Dietary Fiber terhadap Kesehatan Penderita Diabetes Mellitus Tipe 2 - Syarafina Ilma Rahmani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Type 2 diabetes mellitus (DMT2) is a chronic non-communicable disease whose prevalence continues to increase globally, putting significant strain on the healthcare system. One promising intervention approach in DMT2 management is the use of dietary fiber, which is thought to be able to affect glucose metabolism and lipid profiles, including High-Density Lipoprotein (HDL) levels. This study aims to analyze the impact of dietary fiber interventions on HDL levels in DMT2 patients through a meta-analysis approach. The study conducted a systematic search of relevant scientific articles in various leading databases, with strict inclusion criteria to ensure the validity of the data. Meta-analysis is used as the primary method to integrate results from various primary studies that have met the criteria. The results of the analysis showed that dietary fiber interventions had potential benefits in increasing HDL levels in DMT2 patients, although the effects varied depending on the type of fiber, duration of the intervention, and population characteristics. These findings support the use of dietary fiber as part of complementary nutritional strategies in DMT2 management, particularly in improving lipid profiles. The study recommends further research with more standardized intervention designs to strengthen the evidence and clarify the biological mechanisms underlying the effects.